2003
DOI: 10.1111/1475-679x.00097
|View full text |Cite
|
Sign up to set email alerts
|

The Sale of Assets to Manage Earnings in Japan

Abstract: In this article we investigate Japanese managers’ use of income from the sale of fixed assets and marketable securities to manage earnings. The earnings management target examined is Japanese managers’ forecasts of current–year earnings. We find a negative relation between income from asset sales and management forecast error. When current reported operating income is below (above) management's forecast of operating income, firms increase (decrease) earnings through the sale of fixed assets and marketable secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
107
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(124 citation statements)
references
References 23 publications
11
107
1
5
Order By: Relevance
“…Inoue and Thomas (1996), Poitras et al (2002) and Herrmann et al (2003) indicate a positive correlation between firm size and AS. Following Herrmann et al (2003), the log of total assets (SIZE) and prior AS (AS t−1 , found to be positively correlated with AS in a current quarter) are included as the control variables.…”
Section: Control Variables To As and Asdummy Equationsmentioning
confidence: 97%
See 3 more Smart Citations
“…Inoue and Thomas (1996), Poitras et al (2002) and Herrmann et al (2003) indicate a positive correlation between firm size and AS. Following Herrmann et al (2003), the log of total assets (SIZE) and prior AS (AS t−1 , found to be positively correlated with AS in a current quarter) are included as the control variables.…”
Section: Control Variables To As and Asdummy Equationsmentioning
confidence: 97%
“…Therefore, the ratio of debt to equity (D/E) is included as a control variable for differences in leverage. The literature also documents that growth opportunities have a significant, negative correlation with DA (Park and Park 2004) and AS (Herrmann et al 2003). In connection to previous studies, the Book-to-Market ratio (B/M) is included as a proxy for growth opportunities.…”
Section: Control Variables To All Equationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, the examination of related party transactions in the US context indicates the association of related party transactions with earnings management (Gordon and Henry, 2005). Additionally, earnings management can also be used through the sales of assets (Herrmann et al, 2003).…”
Section: Research and Hypotheses Development: According Tomentioning
confidence: 99%